Monitoring dementia and stroke comorbidity in Canada: Prevalence and mortality time trends among individuals aged 65+, from 2003–2004 to 2016–2017. (31st December 2021) - Shaver, Larry C; Toews, Jennette; Plebon‐Huff, Sieara; Pelletier, Catherine; Robitaille, Cynthia; Mcrae, Louise
Abstract: Background: Dementia and stroke are debilitating and interrelated conditions. This study describes the time trends in prevalence and mortality of comorbid stroke and dementia in Canada, among individuals aged 65+. Method: Using data from the Canadian Chronic Disease Surveillance System (CCDSS) for Canadians aged 65+, Joinpoint analyses were conducted to estimate change over time (2003–2004 to 2016–2017) in the age‐standardized prevalence and all‐cause mortality of comorbid dementia and stroke. Validated case definitions were applied to longitudinal CCDSS linked administrative health data to identify comorbid cases (regardless of the sequence of disease identification). Diagnosed cases for both conditions were identified since 1996–1997, but a run‐in period was applied until 2003–2004 to allow a better capture of prevalent cases. Time trends were significant (unless otherwise noted), but differences between sexes were not significant. Result: From 2003–2004 to 2016–2017, the age‐standardized prevalence of the comorbidity increased from 1.4% (∼64, 000 individuals) to 1.7% (∼110, 000 individuals), representing an average annual percent change (AAPC) of 1.1% (females: 1.0%; males: 1.3%). The increase was more pronounced at the beginning of the period and among those aged 80‐84, 85‐89 and 90+. In contrast, during the same period, the age‐standardized prevalence rate among individuals with dementia/without stroke increased with an AAPC of 1.5% (females: 1.5%; males 1.7%), but only with an AAPC of 0.2% (not statistically significant) among those with stroke/without dementia. Following the general declining mortality pattern observed in the Canadian population, the age‐standardized all‐cause mortality rate for those with the comorbidity decreased (AAPC ‐1.4%; females: ‐1.2%; males: ‐1.7%), with a steeper reduction over the first portion of the period. However, Canadians without the comorbidity benefited from a greater decline in all‐cause mortality (AAPC ‐2.2%; females: ‐2.1%; males: ‐2.5%). Conclusion: This surveillance analysis explores the prevalence and all‐cause mortality of dementia and stroke comorbidity, by highlighting its evolution over time in older Canadians. Although further research is needed to explain the drivers of these trends, such public health surveillance data can inform health care policies and programs. Other countries could consider the CCDSS model for enhancing surveillance of dementia and its comorbidities.